2018
DOI: 10.1177/1055665618810574
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cleft Care Through Education: The First Simulation-Based Comprehensive Workshop in the Middle East and North Africa Region

Abstract: Objective: To describe the conduct of the first multidisciplinary simulation-based workshop in the Middle East/North Africa region and evaluate participant satisfaction. Design: Cross-sectional survey-based evaluation. Setting: Educational comprehensive multidisciplinary simulation-based cleft care workshop. Participants: Total of 93 workshop participants from over 20 countries. Interventions: Three-day educational comprehensive multidisciplinary simulation-based cleft care workshop. Main Outcome Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 31 publications
(38 reference statements)
3
64
0
Order By: Relevance
“…All participants reported that they would participate again in a similar workshop and recommend it to colleagues. This highlights the potential of these workshops in promoting sustainable cleft care in areas of need through capacity building and education (Kantar, 2019c). The results reported in this manuscript reinforce the potential role of our simulation-based comprehensive cleft care workshop as reproducible model for comprehensive cleft surgery education, with participants continuing to report an overwhelming satisfaction with the workshop.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…All participants reported that they would participate again in a similar workshop and recommend it to colleagues. This highlights the potential of these workshops in promoting sustainable cleft care in areas of need through capacity building and education (Kantar, 2019c). The results reported in this manuscript reinforce the potential role of our simulation-based comprehensive cleft care workshop as reproducible model for comprehensive cleft surgery education, with participants continuing to report an overwhelming satisfaction with the workshop.…”
Section: Discussionsupporting
confidence: 67%
“…Services provided encompass the entire spectrum of cleft care, including surgical, dental, speech, nursing, psychosocial, and nutritional services among others. In line with our commitment to providing sustainable cleft care and building health care capacity in areas of need, we recently strengthened our educational efforts and organized the first simulation-based comprehensive cleft care workshop in the Middle East-North Africa region in April 2018 (Kantar, 2019c).…”
Section: Simulation-based Comprehensive Cleft Care Workhop Organizatmentioning
confidence: 99%
See 3 more Smart Citations